2019
DOI: 10.1002/adts.201800174
|View full text |Cite
|
Sign up to set email alerts
|

Novel Porous Boron Nitride Nanosheet with Carbon Doping: Potential Metal‐Free Photocatalyst for Visible‐Light‐Driven Overall Water Splitting

Abstract: The band gap of hexagonal boron nitride (h‐BN) is far too wide for efficiently utilizing visible light, limiting its application in photocatalysis. The present study employs first principles calculations to demonstrate that the band gap energies of porous h‐BN (p‐BN) can be tuned by carbon doping to levels appropriate for the absorption of visible‐light, and that the conduction band and valence band match well with the potentials of both hydrogen and oxygen evolution reactions. Importantly, a strategy of carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…In particular, h-BCN synthesis resulted from interest in combining graphene with hexagonal boron nitride (h-BN) to amend the 0 band gap of graphene (G) and the wide band gap of h-BN (typically above 5 eV) simultaneously. As theoretical studies have confirmed, 53 the resulting material (h-BCN) shows an intermediate optical behavior with absorption energy that can be adjusted in the visible range ( e.g ., by varying the BCN stoichiometry), 54 with the possibility of forming segregated domains of one of the three elements (typically C). 55 , 56 As a result, h-BCN is an appealing option for photocatalytic applications, 57 and, apart from water splitting evolution and CO 2 reduction, 56 , 57 h-BCN has recently attracted attention as a catalyst for synthetically relevant photoredox reactions.…”
Section: Two-dimensional Metal-free Photocatalysts: Protagonists Minmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, h-BCN synthesis resulted from interest in combining graphene with hexagonal boron nitride (h-BN) to amend the 0 band gap of graphene (G) and the wide band gap of h-BN (typically above 5 eV) simultaneously. As theoretical studies have confirmed, 53 the resulting material (h-BCN) shows an intermediate optical behavior with absorption energy that can be adjusted in the visible range ( e.g ., by varying the BCN stoichiometry), 54 with the possibility of forming segregated domains of one of the three elements (typically C). 55 , 56 As a result, h-BCN is an appealing option for photocatalytic applications, 57 and, apart from water splitting evolution and CO 2 reduction, 56 , 57 h-BCN has recently attracted attention as a catalyst for synthetically relevant photoredox reactions.…”
Section: Two-dimensional Metal-free Photocatalysts: Protagonists Minmentioning
confidence: 99%
“…In particular, h-BCN synthesis resulted from interest in combining graphene with hexagonal boron nitride (h-BN) to amend the 0 band gap of graphene (G) and the wide band gap of h-BN (typically above 5 eV) simultaneously. As theoretical studies have confirmed, the resulting material (h-BCN) shows an intermediate optical behavior with absorption energy that can be adjusted in the visible range ( e.g ., by varying the BCN stoichiometry), with the possibility of forming segregated domains of one of the three elements (typically C). , As a result, h-BCN is an appealing option for photocatalytic applications, and, apart from water splitting evolution and CO 2 reduction, , h-BCN has recently attracted attention as a catalyst for synthetically relevant photoredox reactions. , König, Wang, and co-workers studied the photochemical C–H functionalization of electron-rich arenes catalyzed by an h-BCN with notable activity, whereas other photo-oxidation and photoreduction reactions were possible by simply tuning the relative content of the h-BCN precursors (typically glucose and boric acid, Figure ). Despite the above-mentioned encouraging case studies, organic photocatalysis by BCN is still in its infancy; therefore, there is fertile soil for future developments.…”
Section: Two-dimensional Metal-free Photocatalysts: Protagonists Mino...mentioning
confidence: 99%
“…Two-dimensional hexagonal boron nitride (h-BN) has planner structure similar to graphene, consisting of alternating B and N atoms linked to one another via strong B–N bonds. , The 2D layers are held together without any bonds hanging between the layers. , The structure of h-BN bestow many important electrical, optical, and chemical properties, showing many potential applications in a variety of fields. Moreover, the properties of h-BN can be elegantly modulated by creating defects, such as boron and nitrogen vacancies. The lone-pair dangling bonds of the vacancies can increase the metal dispersion and provide anchoring sites for single metal atoms. , Defects within the h-BN lattice can be created by electron beam irradiation, solvent exfoliation, ball milling, and other methods. ,, Several studies have reported the use of h-BN as a promising support for catalysis, but most reports are focused on nanocatalysts. , As a support for SACs, h-BN has been mainly investigated using density functional theory (DFT) calculations with limited experimental support. For example, Zhao and Chen reported a computational study on singly dispersed Mo atoms anchored over the defective h-BN monolayer for electrochemical nitrogen fixation .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, doping of graphdiyne nanoribbons (GDYNRs) with BN pairs can result in an appropriate band structure for accelerating catalytic reactions [ 270 , 271 ]. The F-10BN ZZ-GDYNR1 and F-8BN ACGDYNR1 explore the thermodynamics of the OER half-reaction, followed by the adsorbate evolution mechanism (AEM), O–O coupling, and the HER mechanisms ( Figure 13 h).…”
Section: Edge-modification In Nanoribbonsmentioning
confidence: 99%